Pembelajaran Tematik: Pengembangan Media Video untuk Kemampilan Berdiskusi Siswa di Kelas V di Sekolah Dasar - Miftachur Rohmah; Sripit Widiastuti; Dwi Kameluh Agustina (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This study aims to develop thematic learning video media to improve discussion skills of fifth grade students in elementary schools. The scientific approach of the 2013 Curriculum is the basis for development, with a focus on learning methods that encourage active participation and critical thinking. Using the Research and Development (R&D) model adapted from Borg and Gall, this study went through the validation stages of material, media, and language experts. The validation results showed a feasibility percentage of 88.34% for material, 80.60% for media, and 84.45% for language, all in the "very feasible" category. Trials on 20 students showed a positive response with a percentage of 94%. This video media successfully facilitated a more interactive learning experience and increased students' interest and discussion skills. These findings support the use of digital learning media as an effective tool in thematic education in elementary schools.